Aggregation, the skill premium, and the two-level production function - Miguel A. León-Ledesma; Peter McAdam; Alpo Willman (European Central Bank (ECB), 2011)
We examine the two-level nested Constant Elasticity of Substitution production function where both capital and labor are disaggregated in two classes. We propose a normalized system estimation method to retrieve estimates of the inter- and intra-class elasticities of substitution and factoraugmenting technical progress coefficients. The system is estimated for US data for the 1963-2006 period. Our findings reveal that skilled and unskilled labor classes are gross substitutes, capital structures and equipment are gross complements, and aggregate capital and aggregate labor are gross complements with an elasticity of substitution close to 0.5. We discuss the implications of our findings and methodology for the analysis of the causes of the increase in the skill premium and, by implication, inequality in a growing economy.
Keywords: E25; J23; J24; O40; 330; Aggregation; Factor Substitution; Factor-Augmenting Technical Progress; skill-premium; Two-level CES production function